2013
DOI: 10.1007/s10652-013-9297-0
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the internal flow properties and the material exchange interface in an entraining viscous Newtonian gravity current

Abstract: In order to simulate a simple entraining geophysical flow, a viscous Newtonian gravity current is released from a reservoir by a dam-break and flows along a rigid horizontal bed until it meets a layer of entrainable material of finite depth, identical to the current. The goal is to examine the entrainment mechanisms by observing the interaction between the incoming flow and the loose bed. The sole parameter varied is the initial volume of the gravity current, thus altering its height and velocity. The gravity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A "combined run" (where all fluid was seeded) provides detailed velocity measurements in all of the system, but the interface is not shown. The reader is referred to an earlier publication 49 detailing the tracking of the contact discontinuity d(x,t). The reader can see the online video from which Fig.…”
Section: B Newtonian Fluidsmentioning
confidence: 99%
“…A "combined run" (where all fluid was seeded) provides detailed velocity measurements in all of the system, but the interface is not shown. The reader is referred to an earlier publication 49 detailing the tracking of the contact discontinuity d(x,t). The reader can see the online video from which Fig.…”
Section: B Newtonian Fluidsmentioning
confidence: 99%
“…Studies showed that avalanches can increase their mass due to entrainment by multiple factors [Bates et al, 2014;Sovilla et al, 2007] which in turn influences the run-out distance. Even though important, the amount of snow entrained is not the main controlling factor that determines the flow form of the avalanche [Bartelt et al, 2012a].…”
Section: Introductionmentioning
confidence: 99%